Analisis Situasi Gizi dan Kejadian Wasting serta Rekomendasi Intervensi Kecamatan Meurebo Kabupaten Aceh Barat (Studi Kasus di Desa Meurebo) - Ade Mawarni; Marlinda Marlinda; Nora Nora; Selfi Farlia; Surti Evananda T (INDO PUBLISHING, 2026)
Wasting remains a major nutritional problem among children under five and is associated with inadequate nutrient intake, infectious diseases, and poor childcare practices. This study aimed to analyze the nutritional situation related to wasting and evaluate the effectiveness of community-based nutrition education in Meureubo District, West Aceh Regency. A qualitative case study approach was employed using primary data collected through in-depth interviews with nutrition officers and secondary data obtained from the Indonesian Nutritional Status Survey (SSGI), Indonesian Health Survey (SKI), health profiles, and local nutrition program reports. Problem prioritization was conducted using the Urgency, Seriousness, and Growth (USG) method. The findings identified wasting as the highest-priority nutritional problem. Nutrition education involving 29 mothers with infants and toddlers increased the average knowledge score from 88.28 (pre-test) to 95.17 (post-test). Participant satisfaction was also high, with 89.66% reporting satisfaction or high satisfaction. These findings indicate that community-based nutrition education is an effective promotive and preventive strategy for improving maternal knowledge and supporting efforts to reduce wasting among children under five.